Management Ecology and Coastal Area Development Policy Bantul and Kulon Regencies Progo - Muhammad Wahyudi; Erny Poedjirahajoe; Much . Taufik Tri Hermawan; Djumanto (Postgraduate, University of Mataram, 2024)
Management area coast Bantul and Kulon Regencies Progo important done, in discourse connection with system social or activity man often without notice continuity source Power nature and power support the environment or system its ecology. In development, system ecology interprenate come back system policy development in form disturbances environment or phenomenon happen inconsistency on rule legislation That own and high costs for anticipate it. Over each other interpenetration between system that, is important for lower vulnerability and improve resilience area coast through non-formal, formal and political approaches. With use an ecological systems approach is important done and deep study This show that system ecology area coast penetrated by the system policy development is very strong and massive. Research result show that Dynamics each other interpenetration also occurs in the system policy development to system ecology. Variety development ongoing infrastructure massive in time short on the area coastal, has bring up interpenetration come back system ecology